[Sugar cane Froghoppers on cane stalks] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
The Froghopper insects on cane stalks. The froghopper is a serious pest of sugar cane.
Cataloger's title
Keywords: Agricultural pests -- Trinidad and Tobago; Sugarcane—Diseases and pests -- Trinidad and Tobago; Caroni (1975) Limited